Lime Soda Water Softening - Bengtson,Harlan (McGraw-Hill's AccessEngineering., 2014)
Calculating dosages of water softening chemicals, daily chemical requirements, and daily solids production rates requires numerous intermediate calculations after obtaining initial information on source water hardness and plant flow rate. This Excel workbook automates these numerous calculations, saving you time and removing opportunities for error. The workbook calculates required dosages and daily requirements of lime, soda ash (if needed) and carbon dioxide for the lime soda water softening process from inputs of source water hardness, alkalinity and pH along with design plant flow rate. Estimated daily solids production is also calculated. You may select from one of these two processes: 1. Two stage, excess lime process 2. Selective calcium removal process.